Forensic Entomology - Erika Andersen; Russell Mizell; Jessica Kochert; Joy Jordan (EDIS)
Forensics is a hot topic, with many movies and popular television shows (such as “CSI”) introducing youth to the tools, processes, and critical thinking skills needed to solve various crimes. Within this world, insects have a growing presence. The field of forensic entomology focuses on the information that insects provide investigators about the time, location, and criminal negligence within a wide variety of criminal cases. This curriculum is a tool for teaching youth grades 6–8 about the contributions that insects make to the world of forensics. This three-week series of lesson activities is designed for use in after-school programs, summer day camps, and 4-H clubs. However, this package also includes the Next Generation Sunshine State Standards for teachers within formal classroom settings. It was written by Erika Andersen and Russell Mizell with Jessica Kochert and Joy Jordan and published by the UF Department of 4-H Youth Development, January 2011.